Government credit programs: Justification, benefits, and costs - Rosegrant, Mark W.; Siamwalla, Ammar (International Food Policy Research Institute, 1988)
Subsidized credit programs for agricultural producers have often been used to boost production in less developed countries. The "traditional" views in support of this policy instrument, as summarized by von Pischke, Adams, and Donald (1983), are that credit programs are easier to implement than such policies as land reform or infrastructure development, that subsidized credit can offset the negative impact on farm income and disincentives of government policies such as overvalued exchange rates and price controls, and that credit programs are necessary to provide capital for adoption of new technology. The informal credit market moneylenders are considered monopolistic, exploitive, and antidevelopmental, and incapable of providing the necessary credit.